The role of strain path changes on the microstructure, texture, and mechanical properties of unidirectionally and cross-accumulative roll-bonded (ARBed) aluminum - Mohammad Reza Toroghinejad; Saeed Taali; Hamed Asgari; Jerzy A. Szpunar (Journal of Materials Research and Technology, 2023)
Accumulative roll bonding (ARB) was carried out via unidirectional (UARB) and cross (CARB) routes to investigate the role of strain path variation on the microstructure, texture, and mechanical properties of commercially pure Al sheets. The microstructure and crystallographic texture were studied using the X-ray diffraction method. Microstructural observations indicated that the 90-degree sample rotation between consecutive passes led to higher dislocation density in the CARB-processed samples. Moreover, the grain size was remarkably decreased to 193 nm by eight cycles of the CARB technique, showing a reduction of 99% compared to the initially annealed specimen. Macrotexture measurements demonstrated that a strong Cube {001} <100> component (16 × R), observed in the starting Al, disappeared after the first ARB pass. In contrast to the UARBed strips, the Goss/Brass {011} <115>, A {011} <111>, and P {011} <122> components were introduced by sample rotation in CARBed aluminum sheets. The mechanical properties of the processed materials were evaluated using microhardness and uniaxial tensile tests. It was found that the hardness was continuously increased by increasing the number of the pass in both routes. A dramatic drop in the elongation after the first cycle gave rise to a toughness of 6.2 MJ m−3. However, increasing the number of cycles resulted in an increase of about 230% in toughness in the eight-cycle processed specimens.